REVIEW PAPER The concept of prevention as a public health strategy for prostate cancer control - Denis, Louis; Griffiths, Keith; Turkes, Atilla (Archives of Medical Science, 2005)
Prostate cancer is probably present for up to two decades before it becomes clinically evident. Recent improvements in early diagnostic procedures have resulted in an increasing number of men being diagnosed when they are still in the pre-clinical phase of their disease. Early detection, however, has yet to show that secondary prevention leads to any significant decrease in prostate cancer mortality. It logically follows, therefore, that attention must now be directed to the primary prevention of prostate cancer or, at the very least, to restrain the development of the disease to its latent, slowly-growing indolent form. Men of all ethnic groups and from all parts of the world, have a high prevalence of latent prostate cancer. The proportion of these men who develop clinically significant disease does, however, differ widely among different races and in geographical locations. Although this geographical variability in the incidence of clinical cancer would seem most likely to be due to the effect of dietary components on the biological processes implicated in carcinogenesis, evidence of any real associations between specific constituent of a diet and prostate cancer has yet to be determined. Attention would seem to be shifting to the potentially protective effects of specific dietary components, taken as a form of supplementation, but with products that may often have an uncertain composition, unproven efficacy and are not yet monitored by the strict pharmaceutical regulations. Evidence-based research is indeed vital for the scientific evaluation of such dietary constituents, or any other substances that are being considered as chemo-preventive agents for prostate cancer.